2022
DOI: 10.1111/ijfs.15939
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and potential bioactivities of Pacific oyster (Crassostrea gigas)

Abstract: Globally, Pacific oysters (Crassostrea gigas) have a high market demand owing to their increased nutritional value. Crassostrea gigas can be a dietary source to meet the daily nutritional needs. Several studies have evaluated the nutritional value and bioactivity of C. gigas. However, a review of studies examining the nutritional value and bioactivity of C. gigas has not been previously performed. This study aimed to review the studies evaluating the nutritional value and bioactivities of C. gigas components u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…During breeding, it is necessary to optimize the layout of the breeding structure, improve awareness of disease prevention and control, and strengthen breeding management [57], such as controlling the physicochemical and biological factors in the cultivation process to improve immune resistance and reduce the risks to a controllable range [58]. (3) The risk grade of Crassostrea gigas is medium; as a shellfish widely introduced and cultivated around the world, Crassostrea gigas has high nutritional value and market demand [59,60]. Crassostrea gigas have strong adaptability and rapid growth performance, and shellfish are easier to manage in quarantine and transportation than fish and crustaceans.…”
Section: Discussion and Analysis Of Assessment Resultsmentioning
confidence: 99%
“…During breeding, it is necessary to optimize the layout of the breeding structure, improve awareness of disease prevention and control, and strengthen breeding management [57], such as controlling the physicochemical and biological factors in the cultivation process to improve immune resistance and reduce the risks to a controllable range [58]. (3) The risk grade of Crassostrea gigas is medium; as a shellfish widely introduced and cultivated around the world, Crassostrea gigas has high nutritional value and market demand [59,60]. Crassostrea gigas have strong adaptability and rapid growth performance, and shellfish are easier to manage in quarantine and transportation than fish and crustaceans.…”
Section: Discussion and Analysis Of Assessment Resultsmentioning
confidence: 99%
“…Some studies have shown that phenolic compounds found in plants may also play a characteristic as antimicrobial role (Hara‐Kudo et al ., 2004; Huang et al ., 2023; Wu et al ., 2023). These plants, which have high antioxidant effects, can be used to prevent oxidation and to preserve foods, and may also be used in the treatment of diseases (Negara et al ., 2022). Synthetic and natural antioxidants are widely used in the food processing industry.…”
Section: Introductionmentioning
confidence: 99%
“…In Shennong's Herbal Classic of Materia Medica, oysters can prevent and cure windcold, strengthen the body, and extend the life of human beings. Many studies have proven that oysters are a kind of nutritional food, and their active substances have the effects of antibiosis, antioxidation, anti-inflammation, blood sugar lowering, blood pressure, liver protection, and skin whitening (8). At present, the research on oyster nutritional ingredients is mostly concentrated on the preparation of peptides and their application in trauma repair (9), the role of polysaccharides in disease prevention and control (10,11), the distribution and existence form of minerals (12), and many more.…”
Section: Introductionmentioning
confidence: 99%